2016
DOI: 10.1002/cam4.663
|View full text |Cite
|
Sign up to set email alerts
|

The value of breast MRI in high‐risk patients with newly diagnosed breast cancer to exclude invasive disease in the contralateral prophylactic mastectomy: Is there a role to choose wisely patients for sentinel node biopsy?

Abstract: The aim of this study was to evaluate the presence of clinically and mammographically occult disease using breast MRI in a cohort of cancer patients undergoing contralateral prophylactic mastectomy (CPM) and the utmost indication of axillary assessment (sentinel node biopsy (SLNB)) for this side. A retrospective review of patients with unilateral invasive breast cancer or ductal carcinoma in situ (DCIS) from institutional MRI registry data (2004–2010) was conducted. Characteristics of patients undergoing CPM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(84 reference statements)
1
4
0
Order By: Relevance
“…Hence, the overall sensitivity of the screening program is heavily dependent on the frequency of prophylactic mastectomies in the target population and the indication for prophylactic mastectomy. However, our results showed that the cancers found in prophylactic mastectomy specimens were in general small and usually noninvasive, which is in line with findings of previous studies (26,27). Consequently, the importance of detecting these cancers is unknown, even though they are most often…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the overall sensitivity of the screening program is heavily dependent on the frequency of prophylactic mastectomies in the target population and the indication for prophylactic mastectomy. However, our results showed that the cancers found in prophylactic mastectomy specimens were in general small and usually noninvasive, which is in line with findings of previous studies (26,27). Consequently, the importance of detecting these cancers is unknown, even though they are most often…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, there are many studies in which routine SLNB during CPM is not recommended (3,6,7,9,11,13,16,17,(21)(22)(23)(24)(25)(26). In the meta-analysis by Zhou et al (23), the occult breast carcinoma rate was found to be 1.6% in 1343 PMs.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, in what regards MRI, others have argued against its routine use in prophylactic mastectomy, because of its high cost and low sensitivity for the detection of occult carcinoma [ 22 ]. However, MRI is recommended for the surveillance of BRCA1/2 mutation carriers [ 27 , 28 ]; MRI has a high negative predictive value for invasive carcinoma [ 29 ] and can be useful for selecting women who do not need to undergo sentinel lymph node biopsy (because occult carcinomas that have not been identified using MRI have a lower probability of lymph node metastasis) [ 30 ]. Our group reinforces the importance of MRI at a short interval before surgery, since all our patients had a BRCA1/2 pathogenic mutation and, therefore, a higher risk both for occult and for interval carcinoma.…”
Section: Discussionmentioning
confidence: 99%